Bone Loss Rate May Interact with Other Risk Factors for Fractures among Elderly Women: A 15-Year Population-Based Study. (2010) - Sirola, Joonas; Koistinen, Anna-Kaisa; Salovaara, Kari; Rikkonen, Toni; Tuppurainen, Marjo; Jurvelin, Jukka S.; Honkanen, Risto; Alhava, Esko; Kröger, Heikki
Abstract : Aim was to investigate fracture risk (FR) according to bone loss (BL) rate. A random sample of 1652 women aged 53.5 years was measured with dual X-ray absorptiometry in femoral neck in 1989 and 1994 and divided into tertiles of annual BL rate: high >0.84%, moderate 0.13%–0.84%, and low <0.13%. Low trauma energy fractures during following 10 years were recorded. There were no differences in FR between BL tertiles in Cox regression model. Factors predicting lower FR in Cox model were in high tertile: high T-score (HR 0.71; 95% CI 0.54–0.93, P = .012 ), no sister's fracture (HR 0.35; 0.19–0.64, P = .001 ), no mother's fracture (HR 0.52; 0.31–0.88, P = .015 ), in moderate tertile: high T-score (HR 0.69;0.53–0.91, P = .008 ) and good grip strength (HR 0.98; 0.97–0.99, P = .022 ). In low tertile there were no predictors for FR. BL predicted FR in women with mother's fracture in univariate and multivariate model (OR 2.6; 1.15–5.7, P = .021 ) but with sister's fracture this was observed only in multivariate model (OR 2.66; 1.09–6.7, P = .039 ). Accordingly, the risk factors for postmenopausal fractures, especially mother's fracture, may interact with BL.